Dreams and Nightmares : Utopian Visions in Modern Art - Fletcher, Valerie J; Hirshhorn Museum and Sculpture Garden, Washington (Washington : Smithsonian Institution, 1983)
Severini, Gino ; Russolo, Luigi ; Balla, Giacomo ; Sant'Elia, Antonio ; Marchi, Virgilio ; Malevich, Kasimir ; Chasnik, Ilya ; Lissitzky, El ; Malevich, Kasimir ; Chasnik, Ilya ; Tatlin, Vladimir ; Rodchenko, Alexander ; Stenberg, Georgy ; Kandinsky, Wassily ; etc.
Dreams and Nightmares : Utopian Visions in Modern Art, Hirshhorn Museum and Sculpture Garden, Smithsonian Institution, Washington, December 8, 1983 - February 12, 1984
Engels
kunstcatalogus